The construction of the school complaint by the teacher: an integrative review (Research, Society and Development, 2020)
The growing number of students with school complaints referred to specialists has attracted the attention and concern of health and education professionals, who seek to solve the difficulties presented by students. The present study aimed to understand the construction of school complaints by teachers. Therefore, an integrative review of the existing literature on the theme addressed was carried out in May and June, including scientific publications, through the VHL Portal in their respective databases: Latin American and Caribbean Literature on Lilacs Health Sciences, SCIELO and PESPIC. The survey resulted in 8 articles that met the inclusion criteria and evidenced the need for greater articulation and dialogue between Health and Education for prevention and interventions in behavior, learning and emotional problems, which are perceived in the school context. The realization of this integrative review made it possible to verify that the school complaint is in fact a serious problem, which needs to be faced with greater interest and attention by all who make up the school universe, including health professionals, collaborators and school partners.